When More Is Less: Field Evidence on Unintended Consequences of Multitasking - Goes, Paulo B.; Ilk, Noyan; Lin, Mingfeng; Zhao, J. Leon (Management Science, 2018)
Online customer service chats provide new opportunities for firms to interact with their customers and have become increasingly popular in recent years for firms of all sizes. One reason for their popularity is the ability for customer service agents to multitask (i.e., interact with multiple customers at a time) thereby increasing the system “throughput” and agent productivity. Yet little is known about how multitasking impacts customer satisfaction—the ultimate goal of customer engagements. We address this question using a proprietary data set from an S&P 500 service firm that documents agent multitasking activities (unobservable to customers) in the form of server logs, customer service chat transcripts, and postservice customer surveys. We find that agent multitasking leads to longer in-service delays for customers and lower problem resolution rates. Both lead to lower customer satisfaction, although the impact varies for different customers. Our study is among the first to document the link between multitasking and customer satisfaction, and it has implications for the design of agent time allocation in contact centers and more broadly for how firms can best manage customer relations in new service channels enabled by information technology. The online appendix is available at https://doi.org/10.1287/mnsc.2017.2763 . This paper was accepted by Lorin Hitt, information systems.